Peran Pendidikan Dalam Kegiatan Entrepreneurship Santri Kidspreneur Al Madina Surabaya - Ahmad Makinun Amin; M Yunus Abu Bakar (STAI Bumi Silampari, 2021)
Pesantren education is one of the educational institutions that are in great demand by the public because learning is considered more effective and produces good quality human resources in Islamic religious education as well as spiritual values, intellectual education, and emotional education. The education obtained by Pondok Pesantren Al Madinah Surabaya is not only religious education, but there are excellent programs that make students have an entrepreneurial spirit which is expected to later become independent human beings, have good morals, have good language skills and have a high social spirit in society.